Grain and Flour Wheat Quality Modified by Genotype, Availability of Nitrogen, and Growing Season - Cristobal Valdés Valdés; Gaspar Estrada-Campuzano; Carlos Gustavo Martinez Rueda; Aurelio Domínguez López; Ernesto Solis-Moya; Adriana Villanueva Carvajal (International Journal of Agronomy)
The objective of the present study was to determine physical and chemical parameters that determine grain and flour quality of wheat grown in Mexico’s highlands (Toluca, Estado de Mexico) as a response of nitrogen fertilization and growing season. Experiments were carried out in winter-spring 2010 (irrigation) and summer-autumn 2011 (rainfed) season cycles. Nine wheat cultivars were tested under four levels of nitrogen fertilization (N00, N100, N200, and N300 kg N·ha−1) with a population density of 336 seeds m−2. For each growing season and N rate, three replications were performed for each experiment under a randomized complete block design. Best quality indexes were obtained in the winter-spring cycle as a result of genetic variability. Nitrogen availability modified significantly some quality parameters (grain and flour protein, test weight, and hardness) obtaining the highest values at a rate of 100 kg N·ha−1. On the other hand, volume of sedimentation showed positive effects only at a rate of 300 kg N·ha−1. This rate showed positive effects on grain and flour protein, sedimentation volume, and hardness during the summer-autumn cycle. Eneida F94, Tollocan F2005, and Urbina S2007 cultivars presented the highest grain and flour protein content of tested varieties. Finally, Eneida F94 and Tollocan F2005 presented the highest test weight and flour percentage.